Предприниматели-женщины в Украине: путь в бизнес - Исакова, Н.; Кавуненко, Л.; Велтер, Ф.; Смоллбоун, Д. (Социология: теория, методы, маркетинг, 2004)
The paper considers main characteristics and types of female entrepreneurs in Ukraine on the background of results of a study on female entrepreneurship in transition economies. The authors conclude that female entrepreneurship is playing a significant role in modernization of post-Soviet society, changing the attitude of public to women. Entrepreneurial activity has an impact on personal features and settings of a female entrepreneur, and this reduces the number of “reluctant” entrepreneurs and increases the entrepreneurial potential of the nation.